WHITHER ISLAMIC CIVILIZATION? Framing Islamic Education for the Present and Future - Fu’adi, Imam; Naim, Ngainun (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2021)
Traditionally dated from the 8th to the 14th century, historians generally agree on the period of the golden age of Islamic civilization. They count that the keys to this civilizational achievement laid on the flourishing educational institutions, scientific findings, and the births of influential Muslim scholars. This article tries to reframe the significance of education in the creation of Islamic golden age and offer a brief reminder to the importance of education for contemporary Muslim societies. It is a bibliographical study for the materials for the discussion are taken from books, journal articles, and other written sources related to the topic. The collected data were then analyzed by content analysis. This article argues that the state policies on education is the key for the past Muslim golden age. Scientific culture ranging from namely research tradition, translation tradition, reading tradition to scientific habitus are essential in the making of Muslim golden age. This historical records reserves as a reminder for contemporary Muslim to reestablish the past golden age that lies on the reformation of educational system.